Los juegos didácticos en el aprendizaje de la ortografía, del séptimo grado “A”, escuela "Zoila Alvarado de Jaramillo”, Loja 2022- 2023 - Palacios Pineda, Dayana Anavel (2023)
This research work was about Didactic Games in the Learning of Spelling, its general objective was to diagnose the impact of didactic games in the learning of spelling in students of seventh grade "A" at Zoila Alvarado de Jaramillo School, through the application of an improvement proposal. Three specific objectives were developed which were: The first one tried to identify the learning levels related to spelling presented by the students of seventh grade "A"; the second one was to elaborate a methodological proposal through didactic games for the improvement of the students' learning of spelling; the third objective was to evaluate the methodological proposal of didactic games applied for the strengthening of the students' learning of spelling. To carry out this study a descriptive type of research with a mixed approach was used, in the same way a non-experimental design was used, during the same process the following inductive, deductive, analytical, synthetic and statistical methods were applied, the techniques that were used are interview, survey and initial and final evaluation, likewise the instruments used were, the pre and post-evaluation questionnaire, the same that contributed in an effective way to the data collection. The target population was the students of seventh grade at "Zoila Alvarado de Jaramillo" School, 33 students and one teacher were selected. It is essential to emphasize that didactic games help significantly in the teaching and learning of spelling, the students were receptive what the teacher teaches and at the same time it allows to catch the attention of the students, improving participation and cooperation in the classroom. Keywords: Didactic games, spelling, methods, techniques, student-teacher, teaching-learning.